PENGARUH LAMA MARINASI DENGAN AIR KELAPA TERFERMENTASI PADA SUHU REFRIGERATOR TERHADAP KUALITAS FISIK DAGING BROILER BAGIAN PAHA - I Gede Pande Wisnu Gunanda; Dian Septinova; RR Riyanti; Veronica Wanniatie (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of soaking time by using fermented coconut water on physical properties (pH, water holding capacity (WHC) and cooking losses) of thigh broiler meat, and to know the best marinating time for preserving thigh broiler meat. This research was conducted in May 4th--13th, 2020, at Production of Livestock Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The research material used were 18 pieces of broiler thigh meat. This study used a completely randomized design (CRD), with 3 treatments and 6 replications. The applied treatments were broiler thigh meat which was stored in the refrigerator temperature for 7 days (P0), broiler thigh meat marinated with fermented coconut water for 40 minutes, kept in refrigerator temperature for 7 days (P1), and the broiler thigh meat marinated with fermented coconut water for 80 minutes, kept in a refrigerator temperature for 7 days (P2). The variables observed were pH value, water holding capacity (WHC), and cooking losses. The data obtained were then analyzed by Analysis of Variance (ANOVA) at 5% significance level. Results that had a significant effect were further tested using the Least Significant Difference (LSD). The results showed that marinating time had a significant effect (P<0,05) on pH and water holding capacity of broiler meat, but no significant effect (P>0,05) on cooking losses of broiler meat. Keywords: Broiler meat, Fermented coconut water, Marination, Physical quality, Storage time